In situ visualization of a simple bipartite kinetochore with a single microtubule attachment in Giardia intestinalis (Metamonada) - Tůmová, Pavla; Nohýnková, Eva; Wanner, Gerhard (European journal of cell biology, 2022)
To understand general features in evolution of kinetochore organization, investigating a wide range of mitotic mechanisms in various non-model eukaryotes is necessary. A binucleate flagellate Giardia intestinalis is a representative of highly divergent eukaryotic lineage of Metamonads. FIB/SEM tomography was used to investigate ultrastructural details of its mitotic architecture, including kinetochores. Giardia undergoes semi-open mitosis, with the nuclear envelope remaining intact except for polar fenestrae, allowing microtubules to enter the nucleoplasm. At the onset of mitosis, the nuclear envelope bends inward, forming a concave depression at the spindle poles. Spindle microtubules emanate from a cytoplasmic fuzzy microtubule organizing center near the flagellar basal bodies. Kinetochoral microtubules enter the nucleoplasm and bind to kinetochores. A small bipartite kinetochore composed of a dense inner disk, approximately 46 nm in diameter, and a two-armed outer fork, is attached to just one microtubule. To our knowledge, this is the first in situ evidence of a one-microtubule attachment to a kinetochore, which could represent a basic eukaryotic situation.
Keywords: Mitosis; mikrotubuly; Giardia; Spindle apparatus; FIB/SEM; kinetochory; Kinetochores; Giardia lamblia; mitóza; Microtubules; Kinetochore; Nuclear envelope; aparát dělícího vřeténka; Spindle Apparatus